Stability of polyphenols and carotenoids in strawberry and peach yoghurt throughout in vitro gastrointestinal digestion. Issue 5 (13th May 2015) - Oliveira, Ana; Pintado, Manuela
<x xml:space="preserve">Abstract</x> The aim of this research was to evaluate the influence of in vitro gastrointestinal digestion on the stability and bio-accessibility of phenolic compounds and carotenoids, as well as on the antioxidant activity in strawberry and peach enriched yoghurt.